2018
DOI: 10.1038/s41598-018-22346-1
|View full text |Cite
|
Sign up to set email alerts
|

Universal scaling-law for flow resistance over canopies with complex morphology

Abstract: Flow resistance caused by vegetation is a key parameter to properly assess flood management and river restoration. However, quantifying the friction factor or any of its alternative metrics, e.g. the drag coefficient, in canopies with complex geometry has proven elusive. We explore the effect of canopy morphology on vegetated channels flow structure and resistance by treating the canopy as a porous medium characterized by an effective permeability, a property that describes the ease with which water can flow t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 64 publications
1
34
0
3
Order By: Relevance
“…While a great deal of progress in understanding the role of weak thermal stratification with surface-to-bottom temperature differentials of 1-4 • C has been made [5,[16][17][18][19][20][21][22], future studies are suggested to address the effects of diverse macrophytes commonly occupying a large portion of water on temperature and circulation dynamics in shallow lakes. The development of models that account for various vegetation types, such as floating-leaved and free-floating plants [88], are highly desired to represent their impact on drag and light attenuation conditions. This type of study requires high-fidelity hydrodynamic modeling in a real lake environment, in which flow motions in horizontal and vertical dimensions might be equally significant.…”
Section: Discussionmentioning
confidence: 99%
“…While a great deal of progress in understanding the role of weak thermal stratification with surface-to-bottom temperature differentials of 1-4 • C has been made [5,[16][17][18][19][20][21][22], future studies are suggested to address the effects of diverse macrophytes commonly occupying a large portion of water on temperature and circulation dynamics in shallow lakes. The development of models that account for various vegetation types, such as floating-leaved and free-floating plants [88], are highly desired to represent their impact on drag and light attenuation conditions. This type of study requires high-fidelity hydrodynamic modeling in a real lake environment, in which flow motions in horizontal and vertical dimensions might be equally significant.…”
Section: Discussionmentioning
confidence: 99%
“…The approach from Battiato and Rubol (2014), developed for submerged vegetation, follows the concept of coupling an incompressible fluid flow with a porous medium flow. Although it is conceptually suited for rigid vegetation, this approach was also successfully validated with flexible vegetation (see Rubol et al, 2018). The main advantage of this approach lies in the representation of the drag force by a single parameter, i.e.…”
Section: Battiato and Rubolmentioning
confidence: 99%
“…Moreover, additional experiments were carried out in the case of dense canopy. These specific conditions were tested in order to understand difference between models based on Darcy-Brinkman equation (Rubol et al, 2018) and those with a turbulent drag force (Klopstra et al 1997;Meijer and Velzen 1999;Cassan and Laurens 2016).…”
Section: Introductionmentioning
confidence: 99%